Enhancement of extreme ultraviolet emission from laser irradiated targets by surface nanostructures. (11th September 2017) - Barte, E. F.; Lokasani, R.; Proska, J.; Maresova, L.; Kos, D.; Maguire, O.; Joseph, G.; Sheil, J.; O'Reilly, F.; McCormack, T.; Sokell, E.; O'Sullivan, G.; et al.
Abstract: The effects of shape and thickness of a tin surface layer and of the energy of a 170 ps neodymium:yttrium-aluminum-garnet laser pulse on the conversion efficiency (CE) into extreme ultraviolet emission in the 13.5 nm region is investigated. Whereas a CE of up to 1.16% into the 2% reflection band of multilayer Mo/Si optics was measured for a bulk Sn target at a laser energy of 25 mJ, significant CE enhancement up to 1.49% is demonstrated for a 200-nm-thick Sn layer on a microstructured porous alumina substrate.